Legal overview of the types and forms of tourism (Journal of actual problems of jurisprudence, 2018)
This article deals with the legal aspects of types and forms of tourism on the basis of theoretical studies and legislative regulations. Different grounds for classification of tourism are shown. The differences between international and domestic tourism are demonstrated. Special attention is given to the socially oriented types, such as social and ecological tourism. The importance of agro tourism is mentioned.Key words: tourism, tour, ecotourism, visa, social tourism.